2006
DOI: 10.2463/mrms.5.113
|View full text |Cite
|
Sign up to set email alerts
|

Giant Angioleiomyoma in Extremity: Report of Two Cases

Abstract: Angioleiomyomas are smooth muscle tumors that occur most often in the extremities and are usually less than 2 cm in diameter. We present 2 case reports of giant angioleiomyoma. Case 1 was a 51-year-old woman with a 5-year history of a slowly growing mass 12×10 cm in diameter in the right posterior thigh. The tumor was larger than any previously reported. Case 2 was a 72-year-old man with an 8-year history of a slowly growing mass 6×6 cm in diameter in the left palm. The tumor was unique in that it grew to a gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Moreover, we were able to detect that the feeding artery was the medial plantar artery. Nagata et al [14] reported noncalcification, two cases in which the feeding artery was found by threedimensional magnetic resonance angiography.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we were able to detect that the feeding artery was the medial plantar artery. Nagata et al [14] reported noncalcification, two cases in which the feeding artery was found by threedimensional magnetic resonance angiography.…”
Section: Discussionmentioning
confidence: 98%
“…Many are tender to palpation. Leiomyoma occurs predominantly on the lower extremities, less commonly on the head or trunk, and rarely on the hands or in the mouth [4][5][6]. Leiomyomas generally are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Most angioleiomyoma located in the hand do not show direct relationship to arteries, and only few tumors involving arteries have been reported so far [1,2,[11][12][13]15]. There are no specific imaging techniques for angioleiomyoma, but there are reports of 3D CTA imaging [15] and 3D MRI [12] being performed before surgery to help clinicians understand exactly the relationship between a angioleiomyoma and the involved arteries. In the current case, preoperative 3D CTA clearly showed the mass involving the ulnar artery and MRI defined its relationship with adjacent structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The usual treatment for patients having symptoms similar to those in our case is simple excision of the mass and ligation of the feeder vessels [12]. Adequate collateral circulation should be verified both before and during the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation